The Effect of Geometric Shape and Building Orientation on Minimising Solar Insolation on High-Rise Buildings in Hot Humid Climate - Chia , Sok Ling; Ahmad, Mohd. Hamdan; Ossen, Dilshan Remaz (Penerbit Universiti Sains Malaysia, 2007)
High-rise buildings are experiencing overheating condition in hot humid climate. For a high-rise built form, vertical surfaces are the most critical to the impact of solar radiation. This study examines the effect of geometric shapes on the total solar insolation received by high-rise buildings. Two generic building shapes (square and circular) have been studied with variations in width-to-length ratio (W/L ratio) and building orientation using the computer simulation program ECOTECT V5.2. The results revealed that the circular shape with W/L ratio 1:1 is the most optimum shape in minimising total solar insolation. The square shape with W/L ratio 1:1 in a north-south orientation receives the lowest annual total solar insolation compared to other square shapes. This optimum shape (CC 1:1) receives the highest amount of solar insolation on the east-orientated wall, followed by the south-, west- and north-orientated walls respectively. This study guides designers on choosing optimum geometric shape and appropriate orientation for high-rise buildings.